Effect of plant protection chemicals about the fungi Trichoderma harzianum and Purpureocillium lilacinum (Research, Society and Development, 2020)
The fungi in the rhizosphere, soil as Trichoderma harzianum and Purpureocillium lilacinum important antagonists against pathogenic nematodes and root diseases. The objective of the work was to test the compatibility of the microbiological fungicides Ecotrich® and Nenat® with the chemical phytosanitary products used in the treatment of soybean seeds. We tested the following chemicals Avicta® (nematicide and insecticide), Cruiser® (insecticide), Maxim XL® (fungicide), both in their recommended doses. The culture medium the added chemical products were poured into Petri dishes. The fungi were inoculated with the aid of a platinum loop in three equidistant points, totaling 9 colonies of each fungus. The plates were sealed with plastic film (PVC) and maintained in B.O.D. at 25±1 °C temperature, 70±10% RH and 12 h photophase for 10 days. For the control treatment were poured in the Petri dishes PDA culture medium without the addition of chemicals. The compatibility tests were performed in vitro by comparing changes in vegetative growth, sporulation and spore germination compared to the control. The chemicals Avicta®, Cruiser® and Maxim XL®, allowed the growth of colonies of fungi T. harzianum and P. lilacinum. Products Avicta®, Cruiser® and Maxim XL® were classified by biological index as compatible to the fungus T. harzianum. With regard to the fungus P. lilacinum products Cruiser® and Maxim XL® were classified as compatible, but the chemical Avicta® was classified as moderately toxic, and this chemical can have some effect on the fungus P. lilacinum.